2016
DOI: 10.21010/ajtcam.v14i1.31
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Alkaline Α-Amylase Production by Thermophilic Bacillus Subtilis

Abstract: Background: Starch-degrading amylase enzyme is important in biotechnological applications as food, fermentation, textile, paper and pharmaceutical purposes. The aim of current study to isolate alkaline thermostable α-amylase bacteria and then study the composition of medium and culture conditions to optimize cells growth and a-amylase production. Materials and Methods: Thermophilic amylase producing bacterium was isolated from local hot water-springs in Gazan city Saudi Arabia. Results: Phylogenetic analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
2
7
1
1
Order By: Relevance
“…Then, the phylogenetic tree for these different species of Bacillus indicated that the strain was closely related to B. subtilis strain JCM 1465. This result is in agreement with a study that reported the optimization of amylase production by thermophilic B.subtilis (Al-Johani et al 2017). Additionally, Vijayalakshmi et al (2013) reported that Bacillus subtilis produces a more stable protease enzyme compared with B. licheniformis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Then, the phylogenetic tree for these different species of Bacillus indicated that the strain was closely related to B. subtilis strain JCM 1465. This result is in agreement with a study that reported the optimization of amylase production by thermophilic B.subtilis (Al-Johani et al 2017). Additionally, Vijayalakshmi et al (2013) reported that Bacillus subtilis produces a more stable protease enzyme compared with B. licheniformis.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, the formation of colorless hydrolytic zone around the bacteria is an indication of the carbohydrase activities. Then, the clear zone around the colonies in starch and inulin medium is an indication that the starch and inulin have been hydrolyzed by the amylase and inulinase, whereas the dark blue zone is formed through the reaction between carbohydrate and iodine (Al-Johani et al 2017). Furthermore, several studies have been conducted regarding bacteria inulinase activities.…”
Section: Discussionmentioning
confidence: 99%
“…H7. These results are supported by the previous reports stated that the amylase production was increased when soluble starch was used as carbon sources [ 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…Al-Johani ve ark. [18] optimuminkübasyon süresini 48 saat, optimum pH 8.5 ve sıcaklığı 45°C belirtmişlerdir. Asgher ve ark.…”
Section: Deterjan Etkisi 4 Sonuçlar Ve Tartışmaunclassified